Faktor Individual Penyebab Korupsi Dalam Perspektif Islam - Norapuspita, Norapuspita; Djasuli, Mohamad (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
From the perspective of Islam, acts of corruption are acts that lead to losses and are included in disgraceful acts. Individual factors that cause corruption, according to Islam, are things that must be avoided. The discussion on individual factors based on GONE Theory is explained by means of literature studies and from an Islamic point of view. Greed and maslahah that are not in accordance with Islamic teachings can cause losses, one of which is corruption or ghulul. So by avoiding the two individual factors that cause corruption in the form of greed and inappropriate maslahah, it can bring goodness and reduce the possibility of corruption.